Impoverishment Due to Out-of-pocket Health Expenditures: Measurement and Comparison Across Different Surveys in India. Issue 2 (August 2019) - Goyanka, Roopali; Garg, Charu C.; Prasad, Sheela
Various estimates of impoverishment on account of out-of-pocket expenditure (OOPE) on health are available for India, covering different time periods, but there is a void in terms of comparable estimates. This article uses national level surveys conducted by National Sample Survey Organization for measurement of living standards (Consumption Expenditure Survey [CES]) for 2004–2005 and 2011–2012 and Health and Morbidity Survey (HMS) for 2004 and 2014 to quantify the trends in impoverishment estimates over time and identify the factors explaining these trends. Using consistent methodology, it is estimated that the increase in the number of persons impoverished due to OOPE using HMS is 19.78 million (from 77.9 million to 97.78 million) between 2004 and 2014, while using CES, the increase is 2.90 million (from 51.48 to 54.38 million) between 2004–2005 and 2011–2012. Expenditure on outpatient care including drugs led to 72 million people being pushed below poverty line in 2014. Most of the increase in impoverishment has come in lower income quintiles both in rural and urban areas. Government needs to focus on reducing OOPE for bottom three income quintiles and more specifically the household expenditure on medicines.